New psychometric evidence of the labor commitment scale in Peruvian teachers - Amasifuen-Reategui, Manuel; Cruz-Tarrillo, José Joel (Frontiers in Education, 2025)
We live in a highly competitive environment where work commitment has a crucial advantage within educational organizations, given its direct link to performance, productivity, and employee well-being. This study aims to validate the ESCOLA work commitment scale in Peruvian secondary school teachers. The study was approached from an instrumental methodology, applying the survey to 598 teachers in public secondary schools in Peru. Descriptive analyses, scale statistics, and confirmatory factor analysis were performed to determine the structure of the construct. The results indicate that the ECSOLA maintains a reliability in each of its items; its Cronbach’s index ranges between 0.804 and 0.825, whose indices (CFI = 0.927, TLI = 0.901, and RMSEA = 0.076) indicate an adequate adjustment and a one-dimensional scale of 10 items valid to be applied in this context. In conclusion, the findings support the applicability of the scale in the Peruvian educational field, providing a reliable tool to measure teacher engagement and facilitating research on well-being and performance in the educational context.